Influence of Rubber Composition on Mechanical Properties - Vašina, Martin; Pöschl, Marek; Zádrapa, Petr (Manufacturing Technology Journal, 2021)
The purpose of this contribution is to investigate different mechanical properties of various types of rubber composite materials that were filled with carbon black nanofiller. The rubber composites were produced from three different basic rubbers. Moreover, the composites were produced with different volume concentrations of the basic rubbers including their various ratios. Mechanical properties of the tested rubber composites were investigated by means of tensile testing, Shore hardness, rebound resilience, mechanical friction, abrasion, visco-elastic behaviour and vibration damping measurements. It was found in this study that the rubber composition has a significant influence on the stiffness of the investigated rubber composites, and thus, on their mechanical properties.
Keywords: Rubber Composites; Mechanical Properties; Vibration Damping; Friction; Viscoelasticity.